Impact of COVID-19 lockdown in children with neurological disorders in Italy. Issue 2 (April 2021) - Bova, Stefania Maria; Basso, Martina; Bianchi, Marta Francesca; Savaré, Laura; Ferrara, Giusi; Mura, Eleonora; Redaelli, Maria Gaia; Olivieri, Ivana; Veggiotti, Pierangelo; ,; Alfei, Enrico; Olivotto, Sara; et al.
Abstract: Background: The costs and benefits of full lockdown measures are debated. Neurologically impaired children are a vulnerable population with specific needs in terms of protection against infection and access to health services. Objectives: We investigated the effects of lockdown on the health of children with neurological disorders and on their access to care during lockdown. Methods: Data from 514 children (282 males – 232 females) were collected through physician-administered interviews to investigate: the occurrence of viral-like physical symptoms, the correlation between the risk of developing such symptoms and several demographic and clinical variables, the occurrence of any worsening of the children's neurological conditions during lockdown, and their access to care services during this period. Results: 49.1% experienced at least one symptom during the study period, but no child developed severe complications. The prevalence of symptoms was significantly lower during lockdown than during the previous two months. The underlying neurological condition worsened in 11.5% of the patients. Children who regularly left the home during lockdown were greater risk of exhibiting symptoms. During lockdown, 67.7% had a specialist appointment cancelled, 52.6% contacted their paediatrician, and 30.9% contacted their child neuropsychiatrist. Among patients who usually receive rehabilitation, 49.5% continued remotely. Conclusion: Lockdown protected children from infections. Telemedicine and telerehabilitation constituted a valid alternative for the care and treatment of these children, but they should not become a widespread and definitive model of care. COVID-19 and other emergency response plans must take into account the specific needs of children with disabilities.